2009
DOI: 10.1103/physrevlett.102.147204
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Stochastic Domain-Wall Depinning in Magnetic Nanowires

Abstract: Abstract:The stochastic field-driven depinning of a domain wall pinned at a notch in a magnetic nanowire is directly observed using magnetic X-ray microscopy with high lateral resolution down to 15 nm. The depinning-field distribution in Ni 80 Fe 20 nanowires considerably depends on the wire width and the notch depth. The difference in the multiplicity of domain-wall types generated in the vicinity of a notch is responsible for the observed dependence of the stochastic nature of the domain wall depinning field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
109
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 24 publications
9
109
0
Order By: Relevance
“…As the wire width increases, the magnetostatic field from the surface charges becomes weak; T 2 /(w 1 t) thereby decreases. T 1 /(w 1 t) related to the exchange energy difference also decreases because the DW width becomes larger as the nanowire becomes wider [16,27]. As the denominator does not change, the decrease of T 2 /(w 1 t) and T 1 /(w 1 t) leads to the decrease of the depinning field, as can be seen from Eq.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…As the wire width increases, the magnetostatic field from the surface charges becomes weak; T 2 /(w 1 t) thereby decreases. T 1 /(w 1 t) related to the exchange energy difference also decreases because the DW width becomes larger as the nanowire becomes wider [16,27]. As the denominator does not change, the decrease of T 2 /(w 1 t) and T 1 /(w 1 t) leads to the decrease of the depinning field, as can be seen from Eq.…”
Section: Resultsmentioning
confidence: 55%
“…3. Im et al experimentally explored [16] the nanowire width dependence of the depinning field when the aspect ratio is set to about 50%. They also found a similar wire width dependence of the depinning field.…”
Section: Resultsmentioning
confidence: 99%
“…The use of geometrical features to control the DW position is complicated by the magnetic interactions, often depending on the DW structure and its propagation direction [9,19,20,24,25]. Furthermore, the depinning of nominally identical DWs from wire defects or junctions is subject to thermally driven stochastic processes that broaden the range of switching fields compared with simple propagation in the wire [10,12,26].…”
Section: Basic Observationsmentioning
confidence: 99%
“…The structure of these walls is often described as either 'transverse' (figure 1a), with magnetization rotating in an identical direction through any line across the wall, or 'vortex' (figure 1b), in which the DW magnetization circulates internally through 360 • . DWs can alternate between these two structures during propagation [8] and there are many variations from these broad categories [9,10]. A detailed review of the behaviour of DWs can be found elsewhere [11].…”
Section: Basic Observationsmentioning
confidence: 99%
“…22) A relatively large DW (∼a few hundreds nm) was thought to limit the density of devices. 21,40) An extremely large driving current density (>10 12 A=m 2 ) was the greatest barrier for device application since it causes stochastic DW motion 40,41) as well as severe Joule heating. 42,43) Naturally, researchers turned their interest to another magnetic materials to solve the problems raised.…”
Section: Progress In Study Of Current-induced Domain Wall Motionmentioning
confidence: 99%